Safety and immunogenicity of the bi-cistronic GLS-5310 COVID-19 DNA vaccine delivered with the GeneDerm suction device. (March 2023) - Kim, Woo Joo; Roberts, Christine C.; Song, Joon Young; Yoon, Jin Gu; Seong, Hye; Hyun, Hak-Jun; Lee, Hyojin; Gil, Areum; Oh, Yeeun; Park, Ji-eun; Jeon, Bohyun; Lee, Ji-Eun; et al.
Highlights: This study reports the safety and immunogenicity of the GLS-5310 DNA vaccine through 48 weeks. First clinical application of the GeneDerm suction device for DNA vaccine delivery. GLS-5310 was well tolerated and without vaccine-associated severe adverse effects. T cell responses of ∼1200 site forming units/10 6 peripheral blood mononuclear cells were maintained through 48 weeks. T cell responses were many-fold higher than all other vaccine platforms. Antibody responses were induced in 95.5% and maintained through 48 weeks. Abstract: Objectives: The CoV2-001 phase I randomized trial evaluated the safety and immunogenicity of the GLS-5310 bi-cistronic DNA vaccine through 48 weeks of follow-up. Design: A total of 45 vaccine-naïve participants were recruited between December 31, 2020, and March 30, 2021. GLS-5310, encoding for the SARS-CoV-2 spike and open reading frame 3a (ORF3a) proteins, was administered intradermally at 0.6 mg or 1.2 mg per dose, followed by application of the GeneDerm suction device as part of a two-dose regimen spaced either 8 or 12 weeks between vaccinations. Results: GLS-5310 was well tolerated with no serious adverse events reported. Antibody and T cell responses were dose-independent. Anti-spike antibodies were induced in 95.5% of participants with an average geometric mean titer of ∼480 four weeks after vaccination and declined minimally through 48 weeks. Neutralizing antibodies were induced in 55.5% of participants with post-vaccination geometric mean titer of 28.4. T cell responses were induced in 97.8% of participants, averaging 716 site forming units/10 6 cells four weeks after vaccination, increasing to 1248 at week 24, and remaining greater than 1000 through 48 weeks. Conclusion: GLS-5310 administered with the GeneDerm suction device was well tolerated and induced high levels of binding antibodies and T-cell responses. Antibody responses were similar to other DNA vaccines, whereas T cell responses were many-fold greater than DNA and non-DNA vaccines.